Etyka: Część I : Koncepcje etyki (Dydaktyka Filozofii, 2016)
Etyka/Ethics This comprehensive guide to ethics covers fundamental issues raised by meta-ethics, normative ethical theories and applied ethics. It provides a great overview of the great ethical traditions. Particular emphasis was placed on the methodological status of ethical studies, methods we use in moral deliberations and worldview issues, which in the case of ethics becomes of fundamental importance. Different dimensions of moral life justifies the need to draw on other disciplines. For this reason, there are articles in moral psychology, neuroscience, sociology of morality, legal ethics, moral economy, and moral theology. Moreover, the volume takes up concepts of ethics relevant to three significant and influential Christian ethicists – Karol Wojtyła (Pope John Paul II), Tadeusz Styczeń SDS and Tadeusz Ślipko SJ, and – as usual – some issues on teaching ethics. The volume is divided into two parts.